2009
DOI: 10.1007/s10266-008-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of xerostomia (dry mouth)

Abstract: Xerostomia (dry mouth) is a common complaint with widespread implications such as impaired quality of life, oral pain, and numerous oral complications. There are a variety of salivary and nonsalivary causes of xerostomia, the most frequent being medication side effects and systemic disorders. A systematic approach should be employed to determine the etiology of this condition, with distinctions made between patients with subjective complaints of xerostomia alone and those with measurable salivary gland dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
126
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 56 publications
3
126
0
5
Order By: Relevance
“…Approximately 90% of this volume is produced by the salivary glands, and the remaining 10% are produced by numerous minor salivary glands present in the submucosa of the oral and oropharyngeal cavity. 1 Saliva is essential for protection of the mucosa as well as structures of the oral cavity and adjacent gastrointestinal epithelium. 1 In the mouth, saliva participates in the activities of chewing, speaking and swallowing, as well as taste sensitivity, lubrication of tissues, mucosal protection against penetration of various substances, regulation of pH and the formation of an oral biofilm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 90% of this volume is produced by the salivary glands, and the remaining 10% are produced by numerous minor salivary glands present in the submucosa of the oral and oropharyngeal cavity. 1 Saliva is essential for protection of the mucosa as well as structures of the oral cavity and adjacent gastrointestinal epithelium. 1 In the mouth, saliva participates in the activities of chewing, speaking and swallowing, as well as taste sensitivity, lubrication of tissues, mucosal protection against penetration of various substances, regulation of pH and the formation of an oral biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…1 Saliva is essential for protection of the mucosa as well as structures of the oral cavity and adjacent gastrointestinal epithelium. 1 In the mouth, saliva participates in the activities of chewing, speaking and swallowing, as well as taste sensitivity, lubrication of tissues, mucosal protection against penetration of various substances, regulation of pH and the formation of an oral biofilm. Further, saliva helps control oral microbiota, protects teeth against harmful substances and injuries and participates in the remineralisation process.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were collected and maintained at a concentration of 5x10 4 cells/well in 12-wells plates for incubation during 24 hours prior to treatment with Ch/HPMC/P films. After a 24 hour-treatment period and with 1cm 2 of biofilm, the culture medium was removed and the solution of neutral red (50 mg/ml) was added and, after 3 hours of incubation in situ, the plates were washed with phosphate buffered saline (PBS), and a destaining solu-sin, and Masson's trichrome stain for histopathological analysis.…”
Section: Materials and Methods Prepa Rat Ion Of Chitosa N /Hpmc F I mentioning
confidence: 99%
“…It has been demonstrated that multiple causes lead to hyposalivation, including Sjogren's syndrome, diabetes mellitus, sarcoidosis, hepatitis C, adverse effects of pharmacological agents 2 , external beam radiation therapy, patients on radioiodine therapy, tumors and trauma in salivary glands, nutritional deficiencies, and eating disorders such as anorexia and bulimia 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly accepted definition of dry mouth is the subjective sensation of dry m O A he condition has been described as quality of life (Folke et al, 2009). Profound functional impairments have been described as a consequence of the condition including; continuous oral discomfort (Thomson et al, 2006), burning mouth (Ni Riordain et al, 2010) eating and speaking difficulties (Napeñas et al, 2009), problems with wearing dentures (Ikebe et al, 2005), and deteriorating oral health as a result of the dryness F F ar, also describes how some people withdrew from social and persistent impact that dry mouth had upon their oral health and oral health related quality of life.…”
mentioning
confidence: 99%